UVC Germicidal Units: Determination of Dose Received and Parameters to be Considered for N95 Respirator Decontamination and Reuse - Kohli, Indermeet (Photochem Photobiol, 2020)
The COVID‐19 pandemic has resulted in an international shortage of personal protective equipment including N95 filtering facepiece respirators (FFRs), resulting in many institutions using ultraviolet germicidal irradiation (UVGI) technology for N95 FFR decontamination. To ensure proper decontamination, it is crucial to determine the dose received by various parts of the FFR in this process. Recently, our group customized a UVGI unit for N95 decontamination. With experimental and theoretical approach, this manuscript discusses the minimum dose received by various parts of the N95 respirator after one complete decontamination cycle with this UVGI unit. The results demonstrate that all parts of the N95 FFR received at least 1 J cm(−2) after one complete decontamination cycle with this unit. As there are a variety of UVGI devices and different types of FFRs, this study provides a model by which UVC dose received by different areas of the FFRs can be accurately assessed to ensure proper decontamination for the safety of healthcare providers.